Antianginal Agents for the Management of Stable Ischemic Heart Disease: A Review. Issue 4 (July 2016) - Mody, Purav; Sidhu, Mandeep S.; Brilakis, Emmanouil S.; Sacco, Joseph D.; Banerjee, Subhash; Boden, William E.
Abstract : Antianginal medications are an important aspect of optimal medical therapy for the management of angina in patients with stable ischemic heart disease. The lack of a standardized definition of effective antianginal therapy and the lack of clear understanding of the underlying evidence have often been cited as reasons for the large variations in the use of these particular classes of pharmacologic agents in contemporary clinical practice. Hence, we performed a search of the PubMed database and identified published manuscripts examining the effect of common antianginal agents on improving anginal parameters and on important clinical outcomes such as mortality, myocardial infarction, and repeat revascularization from multiple large randomized, controlled trials, systematic reviews, meta-analyses, and outcomes data from observational studies in patients with stable ischemic heart disease. The most commonly used antianginal agents (beta-blockers, nitrates, calcium channel blockers, and ranolazine) demonstrated equivalent efficacy in improving patient reported ischemic symptoms and quantitative exercise parameters. With regards to mortality, beta-blockers are beneficial in the setting of depressed left ventricular systolic function. In contrast, recent evidence points toward the lack of similar benefit of beta-blockers in patients with preserved systolic function, even in the setting of prior myocardial infarction. No survival benefit has been identified with the use of calcium channel blockers, nitrates, or ranolazine. Currently, guidance regarding objective measurement and up titration of antianginal therapy is missing. There is an unmet need for development of potentially novel and clinically relevant methodology to assess the intensity and/or efficacy of antianginal therapy.